Person-Centered Methodologies in the Organizational Sciences: Introduction to the Feature Topic - Morin, A.; Bujacz, A.; Gagné, Marylène (Sage Publications, Inc., 2018)
The 2011 Organizational Research Methods Feature Topic on latent class procedures has helped to establish person-centered analyses as a method of choice in the organizational sciences. This establishment has contributed to the generation of substantive-methodological synergies leading to a better understanding of a variety of organizational phenomena and to an improvement in research methodologies. The present Feature Topic aims to provide a user-friendly introduction to these new methodological developments for applied organizational researchers. Organized around a presentation of the typological, prototypical, and methodologically exploratory nature of person-centered analyses, this introductory article introduces seven contributions aiming to: (a) clarify the meaning, advantages, and applications of person-centered analyses; (b) illustrate emerging prototypical and longitudinal cluster analytic approaches; (c) introduce researchers to multilevel person-centered analyses as well as to auxiliary approaches that will drastically increase the scope of application of these methods; and (d) describe the application of these methods for confirmatory purposes.